Evaluation of an educational programme for people who have difficulty decluttering and organising: A randomised controlled trial in Japan. (22nd December 2021) - Aso, Yasuko; Suzuki, Asuka; Nojiri, Yuka; Mochizuki, Yukiko; Shimozono, Mihoko; Naganuma, Yuki; Yamaoka, Kazue
Abstract: Home clutter can adversely affect work performance, health and well‐being. Clinical‐level hoarding disorders usually manifest during early adolescence, so early detection and prevention of subclinical hoarding tendencies are essential. This study aimed to evaluate a community‐based programme for individuals with poor organising and decluttering skills who volunteered to receive education on how to organise their homes. We conducted an open‐label randomised controlled trial beginning in January 2016 in Tokyo. We enrolled 61 volunteers aged 12–55 years with problems with organising and decluttering. A workshop and home visit group ( n = 30) attended four workshop sessions on organising skills and received a visit from a home organiser. The home visit only group ( n = 31) only received the home organiser visit. The primary outcome was Saving Inventory‐Revised (SI‐R; Japanese version) scores. The secondary outcomes were Clutter Image Rating Scale and Rosenberg Self‐Esteem Scale (Japanese version) scores. Between‐group changes from baseline to 7 months were analysed using a general linear model. At follow‐up, the SI‐R scores of both groups had improved. The mean change from baseline in SI‐R scores was −20.8 (standard deviation = 9.8) and −13.1 (standard deviation = 14.3) in the workshop and home visit and home visit only groups, respectively. The estimated between‐group difference in SI‐R score changes from baseline (adjusted for baseline SI‐R score) was non‐significant at −5.7 (95% confidence interval, −12.4 to 0.9; p = .089). However, the difference was significant in the univariate model: −7.2 (95% confidence interval, −13.7 to −0.8; p = .029). Although both groups improved, after adjusting for baseline values and participant characteristics, there was no significant difference between the groups. Our results suggest that a workshop‐style educational intervention and assistance and advice from professional organisers may help to improve the living conditions of people with hoarding tendencies.